2015
DOI: 10.1007/s11517-015-1358-8
|View full text |Cite
|
Sign up to set email alerts
|

Sound transmission in porcine thorax through airway insonification

Abstract: Many pulmonary injuries and pathologies may lead to structural and functional changes in the lungs resulting in measurable sound transmission changes on the chest surface. Additionally, noninvasive imaging of externally driven mechanical wave motion in the chest (e.g., using magnetic resonance elastography) can provide information about lung structural property changes and, hence, may be of diagnostic value. In the present study, a comprehensive computational simulation (in silico) model was developed to simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 61 publications
1
23
0
Order By: Relevance
“…The tree generated from the algorithm was comparable to the geometry extracted from CT [29-31], which showed monopodiality, and is comparable to the dog lung airways [22]. The generated tree morphology also showed similarity with that reported in previous studies [17,26,33]. …”
Section: Discussionsupporting
confidence: 71%
“…The tree generated from the algorithm was comparable to the geometry extracted from CT [29-31], which showed monopodiality, and is comparable to the dog lung airways [22]. The generated tree morphology also showed similarity with that reported in previous studies [17,26,33]. …”
Section: Discussionsupporting
confidence: 71%
“…; Peng et al. ; Mansy et al 2015a). For example, there is an early airway branching (the tracheal bronchus) that feeds the top right lung lobe that is not usually seen in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Relevant acoustic phenomenon in the pulmonary system have been studied using animal (Kraman and Wang 1990;Mansy et al 2002a;R€ as€ anen et al 2014) benchtop (Acikgoz et al 2008;Dai et al 2015;Mansy et al 2015b) and numerical (Royston et al 1999(Royston et al , 2002Zhang et al 2001;Ozer et al 2007) models. To validate computational models, animal experiments can be carried out (Dai et al 2014a,b;Henry et al 2014;Peng et al 2014Peng et al , 2015. Accurate information on animal airway geometry would be necessary for building realistic models of the airways.…”
Section: Background Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Such identification is crucial for predicting the life of many engineering components. For instance, studies have shown that crack growth is accelerated greatly at the boundary between the slip and stick zones, reducing the fatigue life significantly [25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%